Striped Distribution Pattern of Purkinje Cells of Different Birthdates in the Mouse Cerebellar Cortex Studied with the Neurog2-CreER Transgenic Line. (10th May 2021) - Zhang, Jingyun; Tran-Anh, Khoa; Hirata, Tatsumi; Sugihara, Izumi
Graphical abstract: Highlights: Birthdates of Purkinje cells (PCs) were mapped in Neurog2 -CreER (G2A)::AldocV mice. The birthdate-specific distribution was arranged into unique longitudinal stripes. Each stripe contained PCs born in a particular period between E10.0 and E13.5. A birthdate stripe either matched, included or subdivided a zebrin stripe. The PC birthdate partially determines the zebrin stripe to which a PC belongs. Abstract: Heterogeneity of Purkinje cells (PCs) that are arranged into discrete longitudinally-striped compartments in the cerebellar cortex is related to the timing of PC generation. To understand the cerebellar compartmental organization, we mapped the PC birthdate (or differentiation timing) in the entire cerebellar cortex. We used the birthdate-tagging system of Neurog2 -CreER (G2A) mice hybridized with the AldocV strain which visualizes the zebrin (aldolase C) longitudinal striped pattern. The birthdate-specific distribution pattern of PCs was arranged into longitudinally-oriented stripes consistently throughout almost all lobules except for the nodulus, paraflocculus, and flocculus, in which distinct stripes were observed. Boundaries of the birthdate stripes coincided with the boundary of zebrin stripes or located in the middle of a zebrin stripe. Each birthdate stripe contained PCs born in a particular period between embryonic day (E) 10.0 and E 13.5. In the vermis, PCs were chronologically distributed from lateral to medial stripes. In the paravermis, PCs of early birthdates were distributed in the long lateral zebrin-positive stripe (stripe 4+//5+) and the medially neighboring narrow zebrin-negative substripe (3d−//e2−), while PCs of late birthdates were distributed in the rest of all paravermal areas. In the hemisphere, PCs of early and late birthdates were intermingled in the majority of areas. The results indicate that the birthdate of a PC is a partial determinant for the zebrin compartment in which it is located. However, the correlation between the PC birthdate and the zebrin compartmentalization is complex and distinct among the vermis, paravermis, hemisphere, nodulus, and flocculus.